Temperature control of a biomass gasifier - Rosa, Miguel Ângelo dos Santos (2020)
In recent history, the growing environmental crisis and the unsustainable overuse of fossil fuels have become a catalyst for the development of environmentally friendly or carbon neutron energy sources. Such fact lead to the reemergence of gasification in the research and development community. This technology was prominent during World War II due to the unavailability of oil existent at that time, mostly using coal as fuel. With the end of the war, so came the end of its development. Initially, the literature will be reviewed in order to assess the instrumentation technologies needed to measure the gasification process’ operational parameters, and thus, allow its monitoring and control. In order to facilitate the analysis of the data from the developed instrumentation system, a visualization tool was developed. The literature was then reviewed again in order to find the most suitable model topology for the gasification process. This revealed neural networks as the most reliable model architecture for such endeavor. A gasification model was then devised using experimental data present in the literature. The devised model was then used to establish a simulation and controller design environment. This enabled the development of Model Predictive Controller to control the temperature inside the gasifier. The devised model showed great potential as a prediction model, in spite of the deterioration presented when used as a simulator. The developed controller was able to stabilize the model generated output for all tested set-points. The develop work constitutes a solid ground for future work.